درس الباقلاني لليهودية: من الإلهيات إلى النبوات: (Al-Baqillani’s Study of Judaism: From Divinity to Prophethood) - بدران بن لحسن; إبراهيم محمد زين (At-Tajdid - Intellectual Refereed Journal, 2025)
This research focuses on Al-Baqillani’s study of Judaism through his book Al-Tamhīd, concentrating on two main topics: the proof of Prophet Muhammad’s prophethood and the issue of the abrogation of religious laws within Judaism. Al-Baqillani begins his argument for prophethood by addressing its deniers, such as the Brahmins and others. He then moves on to establish the prophethood of Muhammad ﷺ through miracles, which he categorizes into two types: the Qur’an and tangible miracles. He argues that the Qur’an confirms the finality of prophethood in two ways: its linguistic inimitability and its challenge to the Arabs to produce a similar text, as well as its foretelling of future events. He also asserts that the Qur’an was transmitted through a continuous chain (tawātur), making its authenticity undeniable. Consequently, its connection to Muhammad (PBUH) is established by necessity, whereas the tangible miracles he performed are proven through rational inquiry and evidence. Al-Baqillani then discusses the Jewish position on the abrogation of religious laws, examining the views of various Jewish sects, such as the Shammaites, Ananites, Samaritans, and Isawites, highlighting their differing opinions on the acceptance of prophethood and the possibility of abrogation. He refutes the Jewish claim that the Mosaic Law cannot be abrogated, dismantling their arguments from both textual and rational perspectives. He questions the authenticity of the Torah’s textual evidence and argues that the tawātur (mass transmission) they claim is unreliable. Moreover, he counters their rational objection by asserting that abrogation does not imply divine revision (badāʾ), but rather the adaptation of rulings according to time and place. The research also highlights the influence of Islamic kalām (theology) on Jewish thought. This influence led to the emergence of new Jewish sects that adopted certain Islamic theological concepts in matters such as abrogation, tawātur, and the relationship between reason and revelation. In conclusion, the research underscores the importance of analyzing the methodologies of Muslim theologians in the study of other religions. It also illustrates Al-Baqillani’s role in solidifying discussions on abrogation and the proof of Muhammad’s prophethood within the context of Islamic-Jewish theological debate. Keywords: Al-Baqillani, Judaism, divinity, prophethood, abrogation, Jewish sects.